The Cell Wall Proteome of Marchantia polymorpha Reveals Specificities Compared to Those of Flowering Plants - Kolkas, Hasan; Balliau, Thierry; Chourré, Josiane; Zivy, Michel; Canut, Hervé; Jamet, Elisabeth (Frontiers in Plant Science, 2022)
Primary plant cell walls are composite extracellular structures composed of three major classes of polysaccharides (pectins, hemicelluloses and cellulose) and of proteins. The cell wall proteins (CWPs) play multiple roles during plant development and in response to environmental stresses by remodeling the polysaccharide and protein networks and acting in signaling processes. To date, the cell wall proteome has been mostly described in flowering plants and has revealed the diversity of the CWP families. In this article, we describe the cell wall proteome of an early divergent plant, Marchantia polymorpha, a Bryophyte which belong to one of the first plant species colonizing lands. It has been possible to identify 410 different CWPs from three development stages of the haploid gametophyte and they could be classified in the same functional classes as the CWPs of flowering plants. This result underlied the ability of M. polymorpha to sustain cell wall dynamics. However, some specificities of the M. polymorpha cell wall proteome could be highlighted, in particular the importance of oxido-reductases such as class III peroxidases and polyphenol oxidases, D-mannose binding lectins, and dirigent-like proteins. These proteins families could be related to the presence of specific compounds in the M. polymorpha cell walls, like mannans or phenolics. This work paves the way for functional studies to unravel the role of CWPs during M. polymorpha development and in response to environmental cues.